Neural dynamics of development of nature empathy in children: An EEG/ERP study - Pooja S Sahni; Chirag Rajyaguru; Karan Narain; Kimberly L. Miedenbauer; Jyoti Kumar; Kimberly A. Schonert-Reichl (Current Research in Ecological and Social Psychology)
This paper investigates spatiotemporal correlates of empathic concern for nature using the EEG/ERP method. The assessment of empathic concern for nature is of much utility as it could give us greater insights into conservation behaviors. Research studies investigating the development of empathy in young children inform us about the interplay of affective and cognitive aspects while perceiving other people in distress and its relationship with prosocial behaviors. However, it is not clear how the brain responds while perceiving nature in distress. Nor are the developmental dynamics of empathic concern for nature concretely known. In this study, eighty-three healthy children, 5–12 years (Mean age = 7.65 years and SD = 2.50 years, 35 girls) participated. Analysis of the differences in neural processing when perceiving images of nature in distress and no distress showed a significant main effect of stimulus type. There was a significant difference in the mean amplitudes of early and late ERP components for distress vs no distress, with distress eliciting a pronounced neural response. There were also significant interaction effects of laterality and age with stimulus type. Correlation analysis of differences in early and late components with age suggests shifting dynamics of empathy for nature from affective arousal to cognitive appraisal. In its novel attempt, this study provides neurophysiological support for the development of empathy for nature during childhood.